Estabilização de um sistema com histerese e sujeito a falhas aleatorias - Huamaccto, Elmer Lévano (2014)
This note presents conditions to assure the stability in probability for a hysteresis Bouc-Wen model controlled by a proportional-integral controller subject to random failures in the transmission line. When a failure happens, the controller turns off and remains off for a while. After that, the controller turns on and keeps working until the occurrence of the next failure. The failures occur according to a Poisson distributed process. A numerical example illustrates the result. A real application considering the speed control of a DC motor is presented.